Report of simultaneous measles outbreaks in two different health regions in Portugal, February to May 2017: lessons learnt and upcoming challenges - Augusto, Gonçalo Figueiredo (2019)
In Portugal, measles vaccination coverage and population immunity are high, and no endemic measles cases had been reported since 2004. The World Health Organization classified measles as eliminated in the country in 2015 and 2016, based on data from the previous 3 years. However, in a context of increasing incidence in several European countries in 2016 and 2017, Portugal experienced two simultaneous measles outbreaks with a total of 27 laboratory-confirmed cases (0.3 cases/100,000 population) in two health regions between February and May 2017. Nineteen cases (70.1%) were adults, of whom 12 were healthcare workers. Overall, 17 cases (63.0%) were not vaccinated, of whom five were infants younger than 12 months of age. One unvaccinated teenager died. Genotype B3 was identified in 14 cases from both regions. Measles virus sequencing identified different possible origins of the virus in each region affected. Although measles transmission was stopped in less than 2 months from the first case being notified, these outbreaks represent an opportunity to reinforce awareness of measles diagnosis. We highlight the intensity of the control measures taken and their impact on the rapid control of the outbreaks and also the fact that high vaccination coverage was crucial to stop transmission.